2012
DOI: 10.1371/journal.pone.0051568
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Comprehensive Warm-Up Programs on Proprioception, Static and Dynamic Balance on Male Soccer Players

Abstract: PurposeThe study investigated the effects of FIFA 11+ and HarmoKnee, both being popular warm-up programs, on proprioception, and on the static and dynamic balance of professional male soccer players.MethodsUnder 21 year-old soccer players (n = 36) were divided randomly into 11+, HarmoKnee and control groups. The programs were performed for 2 months (24 sessions). Proprioception was measured bilaterally at 30°, 45° and 60° knee flexion using the Biodex Isokinetic Dynamometer. Static and dynamic balances were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 45 publications
6
110
3
4
Order By: Relevance
“…Some studies have reported an improvement in knee proprioception after training [19,20,21] [21]. Moreover, there was no improvement in ankle position sense after 5-month of ballet training [22].…”
Section: Elite Skiers Display a Better Proprioceptive Acuitymentioning
confidence: 99%
“…Some studies have reported an improvement in knee proprioception after training [19,20,21] [21]. Moreover, there was no improvement in ankle position sense after 5-month of ballet training [22].…”
Section: Elite Skiers Display a Better Proprioceptive Acuitymentioning
confidence: 99%
“…The results show that FIFA +11 is a soccerspecific warm-up program which can improve power, balance, core stability and proprioception (17)(18)(19)(20). It can improve the movement patterns and quality of junior soccer players.…”
Section: Discussionmentioning
confidence: 96%
“…Brito et al (2010) implemented FIFA +11 for 10 weeks (3 times a week) on young male soccer players and reported that muscle strength and balance increased in their knee extensors and flexors (16). It has been reported that FIFA +11 improved soccer player strength, balance and proprioception (17)(18)(19)(20). Nevertheless, the effect of FIFA +11 as a comprehensive warm-up program on FMS test results for assessing the quality of fundamental movement patterns and identifying inefficient movements in individuals has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…FIFA's 11+ and Harmo Knee warm up program also improves the proprioception at 45 and 60 degree of knee flexion and simultaneous increases static and dynamic balance in male soccer players [20].…”
Section: Warm Upmentioning
confidence: 95%